The Development of an Islam-Based Caring Model for Muslim Family Caregivers of Patients with Peritoneal Dialysis in Southernmost Thailand - Sunisa Seephom (Prince of Songkla University, 2023)
Doctor of Philosophy Degree in Nursing (International Program), 2022